Makna di Balik Iklan Traveloka PayLater “Baru Dari Traveloka PayLater!” - Ronaldo Siahaan, Christo (CITRAWIRA : Journal of Advertising and Visual Communication, 2022)
Advertising is a work of art that can be interpreted. In interpreting advertising, there are meanings that appear depending on the perspective used. These meanings can then be used to determine whether an advertisement is good or bad. The good and bad of an advertisement will be seen from a certain point of view, such as the point of view of a critical consumer. From this point of view, an advertisement can be considered informative, relevant, and honest or it can be considered manipulative, irrelevant and deceptive. Advertisement “New from Traveloka PayLater!” has several meanings that can be interpreted from a certain point of view. Although the advertisement is sufficient to describe the advantages of the service, there are some dangers conveyed through the meanings that spread from the beginning to the end of the advertisement. Advertisement “New from Traveloka PayLater!” considered bad because it promotes consumptive behavior and hedonic culture, especially for the millennial generation.